Secretária Executiva: entre as habilidades e as técnicas no mundo dos escritórios - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The working relations of the Executive Secretariat of the public and private organizations of Boa Vista, Roraima was the focus of research. The following question was sought: The interpersonal skills of the Executive Secretariat has been a component of its versatility and an instrument of influence on the employees of the organizations? The objective of the research is to demonstrate the dynamics of interpersonal skills and explain how they become factors of influence of the Executive Secretaries in the daily work of the organizations located in Boa Vista-RR. As for the method historical materialism was the method adopted for the development of the discussions proposed in this research. As for the research design, in the first phase we used bibliographical research. In this phase, the framework of the discussions about immaterial work was identified, the advance of the jobs in the service sector, the profile of the multipurpose and multifunctional worker was indicated. In the next phase, the exploratory and empirical research that occurred between the second half of 2014 and the first and second half of 2015 was applied, with the mapping of the graduates, occupying the position of Executive Secretary in the public and private organizations of Boa Vista-RR. In the field survey, eight organizations accepted that their Executive Secretaries could participate in the research, making a total of twenty-three professionals, who also met the established selection criteria. Documentary research was also used to characterize the subjects of the research. It was a kind of qualitative research. The results indicate that the profession remains conservative in the Bueno-vistense scenario in relation to the prevalence of the female gender, almost all of the women interviewed were in the public service, whether federal or state. The reports of the Executive Secretaries indicated that through interactivity with other collaborators, they build a network of contacts that support them in the performance of their tasks, and in turn constitute a type of "empowerment". It is possible to affirm that the work of the executive secretaries that develop their work activities in the organizations of Boa Vista-RR, includes technical skills and specific knowledge of the area, both foreseen in the academic formation, besides the use of personal attributes that relate to the forms dealing with people and mediating interpersonal relationships. They influence decisions taken by senior management. That the professional performance of the Executive Secretaries is permeated by the exercise of micro-powers. It was concluded that the Executive Secretaries interviewed exercise their profile of multipurpose workers and reproduce social models linked to the social attributes of women in their daily work. And, even if they do not have the formal power, they exert micro-powers of the most varied forms in daily work. That immaterial work, which is understood as the use of personal skills, affections and communication to enable the performance of their activities in their professional environment, occupies a fundamental and indispensable place for the exercise of their respective profession.
Keywords: Secretariado Executivo; Trabalho imaterial; Mulher - Mercado de trabalho; Influência sociocultural; CIÊNCIAS HUMANAS